Hubungan Faktor Sosial Ekonomi dengan Keragaman Konsumsi Pangan Rumah Tangga di Bentang Laut Kepala Burung Papua - Fitryanti Pakiding; Ramadhan Tri Admaja; Dariani Matualage (Igya ser hanjop: Jurnal Pembangunan Berkelanjutan, 2026)
Household dietary diversity is an important indicator for assessing food security and the nutritional quality of families. This study aims to analyze the influence of socioeconomic factors, including maternal education, main source of income, household assets, and distance to the market, on household dietary diversity in the coastal region of the Bird's Head Peninsula, West Papua. This quantitative research applied a household survey across eight coastal areas, and data were analyzed using Chi-Square tests to examine the relationship between socioeconomic variables and dietary diversity. The results show that all tested variables significantly influenced dietary diversity (p < 0.05). These findings highlight the need for context-based and socioeconomic-oriented interventions to improve food and nutrition security in coastal communities.